Cervical Cancer: Epidemiological, Clinical and Therapeutic Aspects Experience of the Mohamed VI Center for Cancer Treatment - Hatim, G.; Chekrine, T.; Alla, M. Ait; Bahri, O.; Belhouari, M.; Bourhafour, M.; Bouchbika, Z.; Benchakroun, N.; Jouhadi, H.; Tawfiq, N.; Sahraoui, S. (British Journal of Healthcare and Medical Research, 2025)
Introduction: Cervical cancer is the second most common gynaecological cancer after breast cancer in low-middle income countries, particularly Morocco. Worldwide, cervical cancer is the 4th most frequently diagnosed cancer and the 4th leading cause of cancer-related death in women. Its pathogenesis is linked to HPV infection. Improved hygiene and living conditions, and the organization of FCV screening, could reduce the incidence and mortality of this neoplasm. HPV vaccination and screening remain the two mainstays of cervical cancer prevention. Aim of the study: The aim of our work is to study the epidemiological, clinical, paraclinical, therapeutic and evolutionary profile of cervical cancer at the Mohamed VI Center for Cancer Treatment. Material and methods: This is a descriptive retrospective study, spread over a six-year period from December 31, 2016 to, January 1, 2010, including all patients diagnosed with cervical cancer and initially managed at the Mohamed VI Center for Cancer Treatment. Results: A total of 168 cases meeting the inclusion criteria were collected. The age group most affected was between 51 and 60. The age of onset of sexual activity was before 18 in 23.8% of cases. Multiparity was noted in 73.82% of cases. 48.8% of patients were using oral contraception. Repeated genital infections were found in 41.07% of patients, the majority of whom were inadequately treated and monitored. Genital bleeding was the main reason for consultation in 89.25% of cases. The mean tumor size was 5 cm, with extremes of 2 and 10 cm. Squamous cell carcinoma predominated with a percentage of 87.5%. Patients were classified according to F.I.G.O 2009 criteria, and stage IIB was most frequently found, with a percentage of 64.2% (108 patients). The most commonly used protocol was concomitant radio-chemotherapy (CRT) followed by brachytherapy in 51.2% of patients. Outcome was specified for 112 patients. It showed locoregional recurrence in 16 patients, lymph node metastases in 2 patients, 1 case of bone metastasis and 1 case of liver metastasis. In our study, estimates of overall survival, progression-free survival and relapse-free survival at 5 years were 71%, 63.2% and 78% respectively. Survival by F.I.G.O. stage was 86%, 78%, 56% and 9% respectively for stages I, II, III and IV. Conclusion: Cervical cancer remains a major public health problem, especially in low and middle income countries where it is a major cause of death. Major advances in diagnosis and treatment occurred in the management of cervical cancer but we still need to step up our screening efforts and extend them to the entire population in order to make impacting breakthroughs.